2002
DOI: 10.1105/tpc.003400
|View full text |Cite
|
Sign up to set email alerts
|

Maize ABI4 Binds Coupling Element1 in Abscisic Acid and Sugar Response Genes

Abstract: Significant progress has been made in elucidating the mechanism of abscisic acid (ABA)-regulated gene expression, including the characterization of an ABA-responsive element (ABRE), which is regulated by basic domain/Leu zipper transcription factors. In addition to the ABRE, a coupling element (CE1) has been demonstrated to be involved in ABAinduced expression. However, a trans factor that interacts with CE1 has yet to be characterized. We report the isolation of a seed-specific maize ABI4 homolog and demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
199
1
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(217 citation statements)
references
References 43 publications
9
199
1
8
Order By: Relevance
“…We searched for 10-to 12-bp sequence motifs overrepresented within 21 to +0.5 kb (relative to transcription start site) of genes in each module and further identified motifs that were significantly similar (q-value < 0.05) to the known plant cis-motifs available in the JASPAR CORE database using TOMTOM program (Gupta et al, 2007). We found that most of the detected motifs were shared among the majority of the modules as exemplified by the motifs that contained exclusively CG-or AT-rich sequences (Supplemental Table 9) with significant similarity to the reported binding sites of ABI4 (a maize AP2-EREBP protein) and SOC1 (an Arabidopsis thaliana MIKC-type MADS box protein), respectively (Riechmann et al, 1996;Niu et al, 2002). Coincidently, four of the five endosperm modules (M10, M12, M15, and M17) included at least one MIKC-type MADS box gene, while all five modules included at least one AP2-EREBP gene based on the current maize genome annotation (Supplemental Data Set 4), indicating that the MIKC-type MADS box and AP2-EREBP families may play broad regulatory roles in maize endosperm development.…”
Section: De Novo Identification Of Cis-motifs Associated With the Endmentioning
confidence: 91%
“…We searched for 10-to 12-bp sequence motifs overrepresented within 21 to +0.5 kb (relative to transcription start site) of genes in each module and further identified motifs that were significantly similar (q-value < 0.05) to the known plant cis-motifs available in the JASPAR CORE database using TOMTOM program (Gupta et al, 2007). We found that most of the detected motifs were shared among the majority of the modules as exemplified by the motifs that contained exclusively CG-or AT-rich sequences (Supplemental Table 9) with significant similarity to the reported binding sites of ABI4 (a maize AP2-EREBP protein) and SOC1 (an Arabidopsis thaliana MIKC-type MADS box protein), respectively (Riechmann et al, 1996;Niu et al, 2002). Coincidently, four of the five endosperm modules (M10, M12, M15, and M17) included at least one MIKC-type MADS box gene, while all five modules included at least one AP2-EREBP gene based on the current maize genome annotation (Supplemental Data Set 4), indicating that the MIKC-type MADS box and AP2-EREBP families may play broad regulatory roles in maize endosperm development.…”
Section: De Novo Identification Of Cis-motifs Associated With the Endmentioning
confidence: 91%
“…More detailed studies have shown that a wide range of functions of ERF proteins are based on their ability to bind to different DNAs that regulate the expression of different downstream genes (OhmeTakagi and Shinshi, 1995;Park et al, 2001;Niu et al, 2002;Chakravarthy et al, 2003;Acevedo-Hernandez et al, 2005;Sasaki et al, 2007). For example, tobacco Tsi1 identifies GCC box and DRE/CRT in responding to biotic and abiotic stresses (Park et al, 2001), whereas ABI4 binds to GCC box, CE1, and S box in ABA, sugar, and light signal pathways (Niu et al, 2002;AcevedoHernandez et al, 2005). Our earlier studies have shown that TERF1 can identify GCC box and DRE/ CRT (Huang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…ABSCISIC ACID INSENSITIVE (ABI) transcription factors are essential for TAG metabolism. ABI4 encodes an Activator Protein-2/Ethylene-Responsive Factor transcription factor that binds the CE1-like element (CACCG) present in many ABA-and sugarresponsive promoters (Finkelstein et al, 1998;Niu et al, 2002;Acevedo-HernĂĄndez et al, 2005). ABI4 is a crucial determinant of ABA sensitivity during TAG breakdown in the embryo (Penfield et al, 2006).…”
mentioning
confidence: 99%